2020
DOI: 10.1155/2020/2348560
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two DNA Metagenomic Bioinformatic Pipelines While Evaluating the Microbial Diversity in Feces of Tanzanian Small Holder Dairy Cattle

Abstract: Analysis of shotgun metagenomic data generated from next generation sequencing platforms can be done through a variety of bioinformatic pipelines. These pipelines employ different sets of sophisticated bioinformatics algorithms which may affect the results of this analysis. In this study, we compared two commonly used pipelines for shotgun metagenomic analysis: MG-RAST and Kraken 2, in terms of taxonomic classification, diversity analysis, and usability using their primarily default parameters. Overall, the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
(75 reference statements)
2
11
0
Order By: Relevance
“…The developers of Kraken tested the original Kraken1 program against a simulated Hi-seq metagenome and found that precision at genus level, defined as the proportion of correctly classified reads from all the classification attempts, was 99.2% [66]. Although this precision is high, and Kraken and Kraken2 have been found by other authors to be precise and accurate and in line with other metagenomic pipelines [67,68], the low numbers of total AOD-associated bacterial reads classified may put our results within the potential margin of error for false positives. The trends we detected in the species level comparisons should therefore be verified, for example using qPCR studies on the oak phyllosphere.…”
Section: Discussionmentioning
confidence: 87%
“…The developers of Kraken tested the original Kraken1 program against a simulated Hi-seq metagenome and found that precision at genus level, defined as the proportion of correctly classified reads from all the classification attempts, was 99.2% [66]. Although this precision is high, and Kraken and Kraken2 have been found by other authors to be precise and accurate and in line with other metagenomic pipelines [67,68], the low numbers of total AOD-associated bacterial reads classified may put our results within the potential margin of error for false positives. The trends we detected in the species level comparisons should therefore be verified, for example using qPCR studies on the oak phyllosphere.…”
Section: Discussionmentioning
confidence: 87%
“…1 Composition of the raw reads for each caribou as per Kraken2, showing the proportions of caribou, human, fungi, green plants, sar (an eukaryotic clade which includes many parasites of animals), bacteria, archaea, viruses, other eukaryotes, and the unclassified reads. Proportions of caribou reads are smaller and non-host and unclassified reads larger for faecal samples (a-d) compared to tissue (e-f) samples ◂ which could not be classified in the faecal samples which could be due to several factors, including database incompleteness or biases (Pignatelli et al 2008;Kibegwa et al 2020), or potentially low quality reads (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Of the known tools, we selected Kraken2, which uses a kmer counting approach for elucidation of the microbial populations from RNA-sequencing data. As previously described, Kraken2 generated accurate taxonomic identification for bacteria with very fast speed [37,38]. However, only a few studies have used Kraken2 for fungal and viral microbiome studies [39,40].…”
Section: Discussionmentioning
confidence: 99%